Mathematics Communication Ability In Mathematics Education Study Program Post Online Learning - Edi Purwanto (Journal of Education and Learning Mathematics Research (JELMaR), 2022)
The COVID-19 pandemic has had an impact on various fields in the world, including education in Indonesia. Based on a preliminary study conducted by researchers, several research results were found related to the effectiveness of distance/online learning which were considered less effective. Research on Difficulties in Learning Mathematics Online During the COVID-19 Pandemic, concluded that learning mathematics becomes difficult and has challenges when learning online for several reasons factors, namely; the limited space for interaction with the teacher, the number of concepts used in mathematics, and the objects studied have abstract patterns. This research is a type of qualitative research that uses descriptive qualitative research methodology. The focus of this research is to describe students' mathematical communication during online learning. The research data were obtained from 6 students of the Mathematics Education Study Program, Pawyatan Daha University. Data collection obtained through test questions and questionnaire sheet. The implementation technique, the test questions contain mathematical problems that have been created to obtain data on students' mathematical communication abilities. The second part contains questionnaire sheet to obtain secondary data related to barriers/students in carrying out learning. The results showed that some students still had low or less communicative abilities, this was indicated by the non-fulfillment of all assessment indicators including strategy, organization and communicative language.